2016
DOI: 10.1016/j.jtusci.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, molecular docking and biological evaluation of imides, pyridazines, and imidazoles derived from itaconic anhydride for potential antioxidant and antimicrobial activities

Abstract: New functionalized N-heterocyclic derivatives were synthesized from an itaconic anhydride (ITA) precursor and characterized by spectral and analytical data. All of the synthesized products were screened for in vitro antioxidant and antimicrobial properties. Among the tested compounds, derivatives 5a and 8a exhibited noticeable DPPH radical scavenging activity, reducing power capacity and nitric oxide scavenging activity compared to standard glutathione. Compound 3d showed strong antibacterial activity, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…At 100 μg/ml, the absorbance value of Cu‐4AP‐Br is above 1.0. This result was similar to a previous study reporting that synthesized compounds (Itaconic anhydride (ITA)) exhibited high reducing power potential . It has been reported that the reducing properties are generally associated with the presence of reductones, shown to exert antioxidant action by donating a hydrogen atom and breaking the free radical chain …”
Section: Resultssupporting
confidence: 91%
“…At 100 μg/ml, the absorbance value of Cu‐4AP‐Br is above 1.0. This result was similar to a previous study reporting that synthesized compounds (Itaconic anhydride (ITA)) exhibited high reducing power potential . It has been reported that the reducing properties are generally associated with the presence of reductones, shown to exert antioxidant action by donating a hydrogen atom and breaking the free radical chain …”
Section: Resultssupporting
confidence: 91%
“…The essential oil and solvent extracts of A. graveolens were reported to exhibit cardioprotective [ 7 ], hepatoprotective [ 16 ], and nephroprotective properties [ 17 ]. In general, the chemical composition of volatile oils varies significantly, depending on a variety of factors, including geographical, soil, and climate conditions, and there have been various studies that have demonstrated the variation in essential oils in Apiaceae species in recent years [ 18 , 19 ]. Swollen joints, redness, joint pain or stiffness, and loss of joint functions are the major symptoms of inflammation, and it is closely associated with an increased production of ROS (reactive oxygen species) and RNOS (reactive nitrogen oxide species) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of compounds 5 a,b was performed by the intramolecular cyclisation of compounds 3 a,b in basic media with conventional and also MW mediated methods with the aim to introduce the 1,2,4‐triazole nucleus into piperazine skeleton, because it is well known that more efficacious bioactive compounds can be designed by joining two or more biologically active heterocyclic systems together in a single molecular framework . In addition, type of compounds 5 a,b can be considered as useful tolls having active SH group for further one pot three component aminoalkylation reactions leading to the formation new bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%